Spud the madness continues - Van de Ruit, John. (London : Penguin Books, 2009)
Spud Milton is in his second year at an elite boys-only private school. He's no longer the youngest or the smallest in the dorm, but if Spud thinks life will be a breeze he is seriously mistaken. He is soon beset with girl trouble, coerced into disastrous late-night adventures by the Crazy Eight, and finds his dream of a famous stage career in tatters.Armed with only his wits and his diary, Spud invites us to delve further into the mind of a boy who discovers that the long, slow road to manhood is never easy as the madness continues . . .
Keywords: Milton, Spud (Fictitious character -- Fiction; Boarding schools -- South Africa -- Fiction; Private schools -- South Africa -- Fiction; Teenage boys -- South Africa -- Fiction; Teenage boys -- South Africa -- Fiction; Single-sex schools -- Fiction; Diary fiction